Studying Carotid Arteries by Echography in Lacunar Infarction Patients - Farrouh, Ibrahim Muhammad; Layka, Issa; Sarhil, Rafik (Journal of medical and pharmaceutical sciences, 2022)
Background: The presence of carotid stenosis (CS) in a patient with lacunar infarction (LI) is usually considered an indication of atherosclerosis and not directly related to the development of this infarction subtype. Aim of the study: This study was designed to determine the relationship between CS and lacunar infarction (LI) and to assess other risk factors for LI. Methods: In a cross-sectional study design we included 70 patients(41male,29 female)older than 40 years among the patients admitted to Neurology department at Tishreen University Hospital,Lattakia,Syria,2019-2020 with clinical and MRI/CT evidence of Lacunar Infarction in the carotid territory, and 70 (36 male,34 female)age and gender-matched control subjects with no neurological diseases. Patients with LI were identified into patients with a single LI and those with multiple LI. We excluded patients with infarcts that were vertebrobasilar or presumed to be cardioembolic. Baseline demographic, and vascular risk factors were recorded. All patients underwent standard carotid ultrasound scans with identifying three grades of stenosis:(low, moderate and high grade). Results: Among 70 LI patients, we found a higher prevalence of ipsilateral low- grade carotid stenosis <50% in 25 patients (38%) compared with the contralateral side in 12 patients (18%), (P <0,001). There was a higher prevalence of Hypertension (HTN) (OR=12, 3. P<0,001), Diabetes Mellitus (DM) (OR=8.P<0,001) and Hyperlipidemia (OR=3, 42.P=0,016) among LI patients. Conclusions: Ipsilateral Carotid Stenosis especially <50% is thought to be an important risk factor for Lacunar Infarction. Hypertention, diabetes mellitus and hyperlipidemia are important risk factors for lacunar infarction.